Effects of COVID-19 on Household Welfare in Benin: A Microsimulation Approach - BASSONGUI, Nassibou; HONLONKOU, N'lédji Albert (AERC, 2023)
The Benin government need to design social policies aimed at reducing employment vulnerability among the population, notably for urban residents, poorest households led by men.